Interaction of organodiselenides with sulphydryl groups at the active sites of some thiol containing proteins - in vitro and in vivo mechanistic studies in mammalian models of diabetes - Kade, Ige Joseph (2008)
The present study sought to compare the in vitro antioxidant potentials of a newly synthesized organodiselenide, dicholesteroyl diselenide (DCDS) and diphenyl diselenide (DPDS) and their possible interactions with some thiol containing enzymes in different tissues from mammalian system. In addition, the potency of DPDS as antioxidant and antihyperglycaemic agents, and its interaction with thiol containing proteins in various mammalian tissues and organs (hepatic, renal and spleenic and more importantly cerebral tissues) were evaluated in animal models of streptozotocin induced diabetic rats. The in vitro results show that DPDS exhibited a higher glutathione-peroxidase mimetic activity as well as increased ability to oxidize both mono- and di- thiols than DCDS. In addition, while DPDS inhibited thiobarbituric acid reactive substances (TBARS) and protein carbonyls formations in both cerebral and hepatic tissues, induced by either iron (II) or SNP, DCDS exhibited a prooxidant effect in both cerebral and hepatic tissues when iron (II) serves as the prooxidant, However, when TBARS was induced by SNP, DCDS slightly modify TBARS formation in both hepatic and cerebral tissues. Also the activities of cerebral and hepatic delata aminolevulinic acid dehydratase (ð-ALA-D), cerebral Na+/K+- ATPase were significantly inhibited by DPDS and only weakly inhibited by the DCDS. Further studies reveal that the inhibition caused by organodiselenides (in this case, DPDS) on Na+/K+-ATPase activity likely involves the modification of the thiol groups at the ATP binding site of the enzyme. Similarly, different isoforms of lactate dehydrogenase (LDH) were significantly inhibited by both DPDS and DCDS in vitro. Likewise, we observed that the in vitro inhibition of different isoforms of lactate dehydrogenase by DCDS and DPDS likely involves the modification of the -SH groups at the NAD+ binding site of the enzyme. Oral administration of DPDS dissolved in soya bean oil administered to streptozotocin induced diabetes in male albino rats shows that there was significant reduction in blood glucose levels accompanied by a marked reduction of glycated proteins in streptozotocin induced diabetic rats treated with DPDS in relation to untreated streptozotocin induced diabetic. In addition, DPDS was able to significantly ameliorate the levels of Vitamin C and GSH (liver, kidney and spleen), which were decreased in streptozotocin treated rats. Similarly, treatment with DPDS was able to markedly abolish the increase levels of TBARS that were observed in STZ diabetes group. Finally, the inhibition of both ð-ALA-D and some isoforms of LDH caused by hyperglycaemia were prevented by DPDS. We also observed that although streptozotocin evoke a significant diminution on brain s antioxidant status and activity of Na+/K+-ATPase, but the activity of acetylcholineesterase and glutamate uptake and release were not altered. However, DPDS was able to markedly restore the observed imbalance in antioxidant status and sodium pump. Finally, we conclude that organodiselenides are promising antioxidant remedy in the management of diseases caused by oxidative stress. However, their toxicity involves an interaction with thiols on proteins and this study has further demonstrated that the sulphydryl groups in question are critical to the normal function of the protein or enzymes. Most likely, these -SH are associated with thiols at the substrate binding (active site) sites of the enzymes. Interestingly, pharmacological doses of organodiselenides 3mg/kg bw for the study on diabetes do not present any observed toxicity.